Effect of row arrangement on yield and monetary benefits in mulberry (Morusindica) + soybean (Glycine max) and mulberry + greengram (Phaseolus radiatus) intercropping - YADAV, B DAYAKAR; KUMAR, T NAGENDRA (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1989-91. to investigate the effect of inter cropping 'Kanva 2' mulberry(Morns indica L.) + soybean [Glycine max (L.),Merr.]; and mulberry + greengram (Phaseolus radiatus L.) on yields ofcomponent crops, total land productivity and Monetary benefits under different row arrangements. Total yield was consistentlygreater in intercropping than in monocropping mainly due to increase in legume population between mulberryplants. Monetary benefits were consistantly higher in intercropping either in mulberry-soybean and or in mulberry +greengram than with the sole mulberry crop. With increase in plant population density both soybean and greengramshowed decline in nodule population. Although intercropping mulberry with soybean or mulberry with greengram gaveup to 40% higher overall yield advantage for the economic viability, mulberry + soybean or mulberry greengram rowarrangement in 1 : 2 ratio proved better.